IMPLEMENTASI PEMIKIRAN IBNU KHALDUN TERHADAP PEMANFAATAN BUDAYA LOKAL DALAM PENDIDIKAN KARAKTER DI SEKOLAH DASAR KOTA BUKITTINGGI - Hendri, Hendri; Hanani, Silfia (Intiqad: Jurnal Agama dan Pendidikan Islam, 2024)
The purpose of this research is to analyse how Ibn Khaldun's thought can be implemented to the local culture that is studied in primary education institutions in Bukittinggi City. This research uses a qualitative method with a descriptive analysis approach using literature studies. Data collected from 65 elementary schools and analysed along with several papers from various literatures related to character education, Ibn Khaldun, and Local Culture. The results of the study show that Ibn Khaldun's thought emphasises that teaching methods that are too harsh can damage the spirit of learning and hinder character development. In addition, the results of this study also show that the utilisation of local culture in education as an impact in using the local content curriculum, namely: Through the use of the concept of education as a process of human acculturation, the process of acculturation is an effort to shape the behaviour and attitudes of a person based on science and skills, and ensure consistency between the objectives of education with the formation of cultured human beings.